Altered lives in a time of crisis: The impact of the COVID-19 pandemic on the lives of older adults in Ireland. Findings from The Irish Longitudinal Study on Ageing - Ward, Mark (TILDA, 2021)
The ongoing pandemic of SARS-CoV-2, a novel coronavirus that causes COVID-19 infection and disease, is threatening healthcare systems globally as well as in Ireland. (1) The COVID-19 pandemic, and public health-associated restrictions, is having a significant impact on the physical, mental, social and economic health and wellbeing of our citizens. No age group is as greatly affected as the older members of our society, with adults aged 65 and over having a 6-8 times increased risk of hospitalisation, and 80% of deaths due to COVID-19 reported among this age group also. (2,3) Older people are at high risk because of age related deficiencies in immune response, the presence of long-term health conditions, problems with mobility, as well as loneliness and social isolation. (4-6) From the recently published TILDA report, The Older Population of Ireland on the Eve of the COVID-19 Pandemic, we know that three-quarters of community-dwelling older adults in Ireland have ≥2 chronic conditions and one-in-six are living with frailty. (7) An earlier chapter (Chapter 2) provides a detailed description of the methodology. Thus, a summary of the methodology used in this chapter is provided here. We use attrition weights as described in the Methodology Chapter to make estimates relevant to the general population aged 60 years and over in Ireland. There are five sections in our analysis. Firstly, we examine general concerns about the COVID-19 pandemic and distribution by sociodemographic factors (age, gender, educational attainment, locality and living alone). Next, we focus on the prevalence of exposure to infection leading to COVID-19 by sociodemographic factors and we report on hospitalisation and requirement for oxygen due to COVID-19. In addition, we ask about infection exposure among members of the household and close contacts. We also investigate the prevalence of COVID-19-related symptoms among TILDA participants themselves and among those close to them such as family, relatives, friends and carers. Finally, we report on mortality among family, relatives and friends of TILDA participants. We report on the distribution of all deaths by sociodemographic factors and we also present the breakdown of deaths by relationship to the participant. We provide descriptive data for the population aged 60 years and over and disaggregate by age group (60-69 years or 70 years and over). A detailed description of these topics and the measures used in these analyses is provided at the start of each section.Data for this chapter come from the COVID-19 Self-Completion Questionnaire (SCQ) completed by TILDA study participants between July and September of 2020. Of the 5,225 participants aged 50 years and older in TILDA at Wave 5, who also participated at Wave 1, 1,410 did not participate in the COVID-19 SCQ, leaving a sample of n=3,815. We remove from our analysis any participant aged less than 60 years of age (n=136) and those participants with missing data for gender (n=10), educational attainment (n=66) and locality (n=1). Thus, the analytical sample includes n=3,602 participants aged 60 years and older. The average age was 71 years, with an age range of 60–98 years.
Keywords: SARS-CoV-2; COVID-19; TILDA; Ageing; Ageing